Speech sound disorders : for class and clinic - Bleile, Ken Mitchell (Plural Publishing, 2020)
This textbook offers a readable and practical guide to the care of speech sound disorders, emphasizing evidence-based principles and procedures that underlie almost all clinical approaches, making this an ideal choice for a wide variety of undergraduate and graduate courses. Nearly twenty-five percent of the chapters offer hands-on analyzes of speech samples from real children.